Antimicrobial Potential of Methanol Extract from Kastuba Leaf (Euphorbia pulcherrima Willd.) - Atwazah Taisir Ibrahim; Kurniasih Suketi; Dyke Gita Wirasisya (Natural B, Journal of Health and Environmental Sciences, 2019)
Some bacteria have been resistant to one or more types of antibiotics, so an effort to find new antimicrobial sources based on medicinal plants is needed. Research that has been done shows that there are 22 types of plants used as wound treatment used by local people of Timbanuh, East Lombok, one of them is kastuba (Euphorbia pulcherrima Willd.). This study was conducted to test the antimicrobial potential of kastuba leaf extract which has been used ethnomedicinely as a wound teratment in Timbanuh. The antimicrobial activity of kastuba extract was tested against Staphylococcus aureus bacteria. This test used 4 samples. Sample 1 (leaf part 1-5, wind dry method), samples 2 (leaf part 6-10, wind dry method), samples 3 (leaf part 11-15, wind dry method), and sample 4 (leaf part 11-15, oven dry method). The measurement of the antimicrobial potential was carried out by the well diffusion method. The results showed that kastuba leaf extract (samples 1 to 4) at concentration 10 mg / 100µL had a inhibition zone of 9,208; 10,041; 10,583; 11,541 mm and 11,85; 12.08; 14.25; 15.92 mm at concentration 20 mg / 100µL. Sample 4 showed larger inhibition zone affected by different drying method used. The conclusion of this study is kastuba leaf extract has the potential as an antimicrobial.